RETRACTED: Digital model of psychophysiological support for university students - Pozharskaya Elena; Basina Natalya; Golosnov Oleg; Popova Svetlana; Rybalka Julia (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001